Secondary prevention of cerebrovascular events in patients with "asymptomatic" atherosclerotic stenosis of the vertebral arteries. (14th October 2021) - Shugushev, Z; Karasev, S; Maximkin, D; Volkov, S; Korobkov, A; Chepurnoy, A; Bagin, S
Abstract: Aim: To determine the feasibility of performing endovascular interventions in patients with "asymptomatic" atherosclerotic stenosis of the vertebral arteries, as a method of secondary prevention of cerebrovascular events. Material and methods: The patients were randomized into 2 groups: in group I (n=78), secondary prevention of cerebrovascular events were carried out in a combined strategy - stenting of the vertebral arteries in combination with medication therapy, and in group II (n=78) - only medication therapy. Group I were randomized in 2 subgroups – Ia and Ib. In subgroup Ia (n=39) – endovascular intervention were performed with embolism protection devices, and in subgroup Ib (n=35) - embolism protection devices were not used. Long-term follow-up was planned after 12, 24 and 36 months. Inclusion criteria: "asymptomatic" stenosis of vertebral arteries 50–95%; the diameter of the vertebral arteries is not less than 3.0 and not more than 5 mm; the presence of not gross cerebral and focal symptoms corresponding to the initial (asymptomatic) stage of encephalopathy (according to E.V. Schmidt). Primary endpoint: total frequency of cerebrovascular events. Results: The total incidence of spasm and dissection during endovascular intervention was 20.5% in subgroup Ia and 2.5% in subgroup Ib (p=0.0367). Also in subgroup Ia, 2 (4.5%) patients had transient ischemic attack. In subgroup Ib, perioperative cerebrovascular events was not observed. The total frequency of major cerebral complications over 36 months of follow-up was 4.5% in group 1 and 37.5% in group II (χ 2 =15.101; p<0.0001). The frequency of cardiac events was 9.1 and 19.6%, respectively, to groups I and II (χ 2 =14.784; p<0.0001). These indicators were obtained against the background of high patient adherence to treatment and high rates of achieving tough target lipid values. Restenosis of the stents was observed in general, in 18% of patients from group I, who underwent stenting of the vertebral arteries by various generations of stents. Moreover, restenosis alone did not affect the incidence of major cerebral complications in the long-term period (χ 2 =0.1643; p=0.735). Conclusion: In spite of the development of restenosis, it is endovascular intervention in combination with drug therapy that helps to avoid the development of large cerebrovascular events arising from the instability of atherosclerotic plaque in patients with "asymptomatic" vertebral artery stenosis and is a reliable method of secondary prevention of of cerebrovascular events. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian academic excellence project 5-100